SARANA DAN METODE PEMBELAJARAN EFEKTIF PESERTA DIDIK DI SEKOLAH DASAR ERA DIGITAL - Firman Mansir; Sofyan Abas; Lia Kian (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2021)
The purpose of writing this article was to find out and explain effective learning methods used and applied in elementary schools in the digital era. In addition, this study could review the lack of utilization and management of facilities in elementary schools. At the time of starting their age, the students needed to get guidance by using a way that was in sync with the situation they were experiencing. Methods that could be used for education were advice, stories, and customs. There were no bad or good methods. Because it depended on many factors. The crucial thing that educators paid attention to in deciding a method was to know the limits of the goodness and weaknesses of the method to be used. As a result, it was possible to formulate conclusions regarding the outcome or achievement of tnegrihe decision objectives. The use of facilities was very crucial for the continuity of the teaching and learning process and increasing the quality of learning for students and educators. The facilities greatly hypnotized the ability of students to learn. This showed that the role of facilities was very crucial in supporting the quality of student learning. Management of facilities was a very crucial activity in schools, the success of learning in schools lied in how the strategic location of schools was placed. This study used a qualitative approach, so that in conducting data analysis the literature analysis method was sourced from various data that had been prepared. Keywords: method, learning, student. References: Anugraheni, I. 2018. Meta Analisis Model Pembelajaran Problem Based Learning dalam Meningkatkan Keterampilan Berpikir Kritis di Sekolah Dasar [A Meta-analysis of Problem-Based Learning Models in Increasing Critical Thinking Skills in Elementary Schools]. Polyglot: Jurnal Ilmiah, 14(1), 9–18. Baharun, H., & Finori, F.D. 2019. Smart Techno Parenting: Alternatif Pendidikan Anak Pada Era Teknologi Digital. Jurnal Tatsqif, 17(1), 52–69. Deshler, D.D., Schumaker, J. B., Lenz, B. K., Bulgren, J. A., Hock, M. F., Knight, J., & Ehren, B. J. 2001. Ensuring content‐area learning by secondary students with learning disabilities. Learning Disabilities Research & Practice, 16(2), 96–108. Gull, F., & Shehzad, S. 2015. Effects of cooperative learning on students’ academic achievement. Journal of Education and Learning, 9(3), 246–255. Hadi, S. 2011. Pembelajaran Sosial Emosional Sebagai Dasar Pendidikan Karakter Anak Usia Dini. Jurnal Teknodik, 15(2), 227–240. Jannah, S. N., & Sontani, U. T. 2018. Sarana dan prasarana pembelajaran sebagai faktor determinan terhadap motivasi belajar siswa. Jurnal Pendidikan Manajemen Perkantoran (JPManper), 3(1), 63–70. Mansir, F. 2020. Identitas Guru PAI Abad 21 Yang Ideal pada Pembelajaran Fiqh di Sekolah dan Madrasah. Muslim Heritage, 5(2), 435. Mansir, F. 2020. Kesejahteraan Dan Kualitas Guru Sebagai Ujung Tombak Pendidikan Nasional Era Digital. Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 8(2), 293–303. Mansir, F. 2020. Management of Fiqh Learning In School an Madrasah For Islamic Religious Education Teacher. Ta’dib: Jurnal Pendidikan Islam, 9(2), 78–85. Mansir, F. 2020. Manajemen Pondok Pesantren di Indonesia dalam Perspektif Pendidikan Islam Era Modern. QALAMUNA: Jurnal Pendidikan, Sosial, Dan Agama, 12(2), 207–216. Mansir, F. 2020. The impact of globalization on islamic education toward fiqh learning existence in covid-19 pandemic period. ATTARBIYAH: Journal of Islamic Culture and Education, 5(2), 123–133. Mansir, F. 2020. The Urgency of Fiqh Siyasah In Islamic Education Learning At Madrasas And Schools. POTENSIA: Jurnal Kependidikan Islam, 6(2), 142–154. Mansir, F. 2020. Urgensi Metode Ceramah dan Diskusi (Buzz Group) dalam Proses Pembelajaran di Madrasah. TADRIS: Jurnal Pendidikan Islam, 15(2), 225–235. Mansir, F. 2021. Aktualisasi Pendidikan Agama dan Sains dalam Character Building Peserta Didik di Sekolah dan Madrasah. J-PAI: Jurnal Pendidikan Agama Islam, 7(2). Mansir, F. 2021. Analisis model-model pembelajaran fikih yang aktual dalam merespons isu sosial di sekolah dan madrasah. Ta’dibuna: Jurnal Pendidikan Islam, 10(1), 88–99. Mansir, F. 2021. Kontribusi Kepemimpinan Kepala Sekolah Dalam Mewujudkan Pendidikan Humanis. TADBIR MUWAHHID, 5(2), 149–166. Mansir, F. 2021. Paradigma Pendidikan Inklusi Dalam Perspektif Pendidikan Islam: Dinamika Pada Sekolah Islam. Tadrib, 7(1), 1–17. Mansir, F. 2021. The Urgency of Fiqh Education and Family Role in The Middle of Covid-19 Pandemic For Students In School and Madrasah. Kamaya: Jurnal Ilmu Agama, 4(1), 1–10. Mansir, F., Parinduri, M. A., & Abas, S. 2020. Implementasi Pendidikan Karakter Melalui Kegiatan Pembinaan Peserta Didik Dalam Membentuk Watak Kuat-Positif. Taman Cendekia: Jurnal Pendidikan Ke-SD-An, 4(1), 429–437. Masturdin, M. 2016. Kreativitas Guru Menumbuhkan Motivasi Belajar Siswa dalam Upaya Peningkatan Hasil Belajar Aqidah Akhlak di MTSN Rukoh Darussalam Banda Aceh. PIONIR: Jurnal Pendidikan, 5(2). Prastyawan, P. 2016. Manajemen Sarana dan Prasarana Pendidikan. Al Hikmah: Jurnal Studi Keislaman, 6(1). Rianie, N. 2015. Pendekatan dan Metode Pendidikan Islam (sebuah perbandingan dalam konsep teori pendidikan Islam dan barat). Management of Education, 1(2). Sadeghi, R., Sedaghat, M. M., & Ahmadi, F. S. 2014. Comparison of the effect of lecture and blended teaching methods on students’ learning and satisfaction. Journal of Advances in Medical Education & Professionalism, 2(4), 146. ShahsavariIsfahani, S., Mosallanejad, L., & Sobhanian, S. 2010. The effect of virtual and traditional methods on students learning and competency–based skills. Hormozgan Medical Journal, 14(3), 184–190. Ummah, M. S. (n.d.). Manajemen Strategi Program Pendidikan Diniyah dalam Pembentukan Karakter Siswa di SMP Negeri 2 Jombang Kabupaten Jombang. Jurnal Meirinawati. 13–28. Yamin, M. 2015. Teori dan Metode Pembelajaran: Konsepsi, Strategi dan Praktik Belajar yang Membangun Karakter. Malang: Madani. Kelompok Intrans Publishing) Anggota IKAPI.